2015
DOI: 10.1126/science.aaa4268
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-3 amplifies acute inflammation and is a potential therapeutic target in sepsis

Abstract: Sepsis is a frequently fatal condition characterized by an uncontrolled and harmful host reaction to microbial infection. Despite the prevalence and severity of sepsis, we lack a fundamental grasp of its pathophysiology. Here we report that the cytokine interleukin (IL)-3 potentiates inflammation in sepsis. Using a mouse model of abdominal sepsis, we show that innate response activator (IRA) B cells produce IL-3, which induces myelopoiesis of Ly-6Chigh monocytes and neutrophils, and fuels a cytokine storm. IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
262
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(272 citation statements)
references
References 35 publications
8
262
1
1
Order By: Relevance
“…36,37 Recently, it was described that IL-3 promotes the production of inflammatory monocytes and neutrophils in a sepsis model. 38 Our data also show significantly increased numbers of monocytes and neutrophils in the spleen and/or bone marrow of mice treated with IL-3. The numbers of mast cells and dendritic cells were not significantly altered in the spleen, kidney, and bone marrow, when 18-week-old MRL/lpr mice were treated for 6 days with anti-IL-3 (50 μg/day) or IL-3 (200 ng/day) (data not shown).…”
Section: Discussionsupporting
confidence: 67%
“…36,37 Recently, it was described that IL-3 promotes the production of inflammatory monocytes and neutrophils in a sepsis model. 38 Our data also show significantly increased numbers of monocytes and neutrophils in the spleen and/or bone marrow of mice treated with IL-3. The numbers of mast cells and dendritic cells were not significantly altered in the spleen, kidney, and bone marrow, when 18-week-old MRL/lpr mice were treated for 6 days with anti-IL-3 (50 μg/day) or IL-3 (200 ng/day) (data not shown).…”
Section: Discussionsupporting
confidence: 67%
“…In a proof-of-concept study, we showed that high IL-3 levels in septic patients are associated with high mortality. 17 A recent study further confirmed the role of IL-3 in the immune regulation and potential response to corticosteroids during sepsis. 19 Translating this discovery into a clinically viable test, however, requires a fast, easy-to-use platform that could overcome the long assay time (5–8 hours) and complexity of a standard enzyme-linked immunosorbent assay (ELISA).…”
Section: Introductionmentioning
confidence: 75%
“…In addition, the roles that cytokines and inflammatory pathways play in sepsis pathogenesis are gradually being elucidated [48,49]. The application of bioinformatics and computerized mathematical models has also contributed to greater knowledge of the pathogenesis of sepsis [27,50].…”
Section: Pathogenesis Of Sepsismentioning
confidence: 99%
“…In addition to anti-TNF therapy, several research efforts have been dedicated to investigating the potential of therapies targeting proinflammatory cytokines in sepsis. Recently, Weber et al [49 ]reported on the role of IL-3 in sepsis and that IL-3 deficiency protects mice from sepsis. This adds to reports that blockade of high-mobility group box 1 (HMGB1) [83], IL-17 [84], IL-1 [85] and many other cytokines was protective in experimental models of sepsis.…”
Section: Targeting Inflammationmentioning
confidence: 99%